Iluminação na conservação preventiva de coleções em museus: estudo de caso no Museu Histórico Abílio Barreto (Belo Horizonte / MG) - Marília Tanure Caram Pereira (2021)
This dissertation discusses the theme of lighting in museums, dealing with the dialectic between exhibiting and preserving, taking into account the fulfillment of luminous comfort requirements and minimization of the risks of photo deterioration of collections. The main objective of this research was to investigate lighting for preventive conservation of collections in museums, through an analysis of the lighting of Abílio Barreto Hystorical Museum, in Belo Horizonte — creating a methodology to achieve adequate lighting for conservation and exhibition of cultural assets, and luminous comfort for users. Methodology included a review of the requirements for good lighting performance in exhibition spaces, fundamental parameters for the preventive conservation of collections, major damage caused by photo deterioration, technical recommendations and state-of-the-art technology to preserve exhibited cultural goods. Illuminance measurements were carried out in loco, observing the NBR 15.215 standard, in vertical and horizontal planes relevant to the exhibition, in two rooms, separating the natural and artificial light components. Static and dynamic simulations of natural lighting were performed using the Climate Studio program. The results cover the description of the lighting strategies used in MhAB, and illuminance isocurves in the studied rooms. Based on the results, an analysis of the lighting strategies at the MhAB is presented, with a focus on preventive conservation of the collection, in balance with the requirements of human luminous comfort, with reference to conservation requirements of collections proposed in the CIE 157 technical report: 2004, such as maximum illuminance levels and maximum annual exposure doses. A zoning of the studied rooms is proposed, indicating which types of collections can be exhibited in each zone, meeting the requirements of CIE 157:2004. Among the conclusions it is highlighted that, although, at first sight, the lighting strategies for luminous comfort and for preventive conservation of the collections seem opposite, they can be complementary, reaching both objectives at the same time, meeting the regulatory requirements.